(untitled) - Maas, Sarah J. (New York, 2017)
Following the shattering of the glass castle and the deaths of his men, Chaol pursues recovery by searching for healers in the southern continent while trying to convince Dorian and Aelin to ally with him and Nesryn in order to avoid war.
HL800
Accelerated Reader
Keywords: Kings, queens, rulers, etc; Fiction